2013
DOI: 10.11646/zootaxa.3750.5.6
|View full text |Cite
|
Sign up to set email alerts
|

Bird fossils from Ankilitelo Cave: Inference about Holocene environmental changes in Southwestern Madagasca

Abstract: The identifications of non-permineralized fossil bird bones recovered from Ankilitelo Cave in southwestern Madagascar are presented. Among the more than 560 elements recovered, 29 different taxa were identified, the vast majority being species that still occur in this region of the island. Eggshell remains from the extinct elephant bird (Family Aepyornithidae) and assigned to Aepyornis sp. were found at the site. Two identified extant taxa, Scopus umbretta and Monias benschi, no longer occur in the area immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Factors that contributed to megafaunal demise continue to be debated. While some researchers have suggested that direct competition with introduced domesticated species or hypervirulent diseases may have killed the megafauna (Dewar , MacPhee and Marx ), most have focused on climate change (increasing aridity), hunting by humans, or anthropogenic habitat alteration (Battistini , Burney and MacPhee , Burney , , Godfrey and Jungers , Burney et al , Kaufmann , Clarke et al , Godfrey and Irwin , Virah‐Sawmy et al , , Crowley , Crowley et al , Godfrey and Rasoazanabary , Crowley and Samonds , Goodman et al , Goodman and Jungers , Burns et al ). Because aridification and anthropogenic deforestation can have similar effects on vegetation, resolving which of these factors (if either) triggered megafaunal extinctions in Madagascar has remained a challenge.…”
Section: Reconstructed Vegetation Change and Inferred Climate During mentioning
confidence: 99%
“…Factors that contributed to megafaunal demise continue to be debated. While some researchers have suggested that direct competition with introduced domesticated species or hypervirulent diseases may have killed the megafauna (Dewar , MacPhee and Marx ), most have focused on climate change (increasing aridity), hunting by humans, or anthropogenic habitat alteration (Battistini , Burney and MacPhee , Burney , , Godfrey and Jungers , Burney et al , Kaufmann , Clarke et al , Godfrey and Irwin , Virah‐Sawmy et al , , Crowley , Crowley et al , Godfrey and Rasoazanabary , Crowley and Samonds , Goodman et al , Goodman and Jungers , Burns et al ). Because aridification and anthropogenic deforestation can have similar effects on vegetation, resolving which of these factors (if either) triggered megafaunal extinctions in Madagascar has remained a challenge.…”
Section: Reconstructed Vegetation Change and Inferred Climate During mentioning
confidence: 99%
“…Most important is the assessment of localities where specimens of extant forms whose fossils are found in sympatry with the recently extinct lemur 'megafauna'. The cave site of Ankilitelo, in southwestern Madagascar, 45 km northeast of the city of Toliara, is one such location [Godfrey et al, 1999;Simons et al, 2004;Muldoon and Simons, 2007;Muldoon et al, 2009;Goodman et al, 2013]. Ankilitelo may be the most recent location preserving extinct forms and sympatric subfossil representatives of extant lemurs, with dates for these primates being as recent as ∼ 500 to ∼ 600 years ago [Simons, 1997;Godfrey et al, 1999;Simons et al, 2004;Muldoon et al, 2009;Goodman et al, 2013].…”
mentioning
confidence: 99%
“…The cave site of Ankilitelo, in southwestern Madagascar, 45 km northeast of the city of Toliara, is one such location [Godfrey et al, 1999;Simons et al, 2004;Muldoon and Simons, 2007;Muldoon et al, 2009;Goodman et al, 2013]. Ankilitelo may be the most recent location preserving extinct forms and sympatric subfossil representatives of extant lemurs, with dates for these primates being as recent as ∼ 500 to ∼ 600 years ago [Simons, 1997;Godfrey et al, 1999;Simons et al, 2004;Muldoon et al, 2009;Goodman et al, 2013]. Although dates for Ankilitelo's primates are very recent (see above), new data from avian bones and eggshells at Ankilitelo suggest that portions of the fossil assemblage here date to as far back as ∼ 13,000 BP [Goodman et al, 2013].…”
mentioning
confidence: 99%
See 2 more Smart Citations